Investigating Student Learning Outcome using Quizziz in Engineering Students (Mobile and Forensics, 2022)
Material control throughout the manufacturing and distribution process is a cycle that needs to be considered in material handling and technology identification so that the production system in the automation industry runs according to its workflow. Industrial automation in vocational learning must be provided so that students have insight related to the field of automation. Vocational learning needs to use appropriate and modern media in the era of digitalization. The purpose of this study was to determine the performance of Quizizz media for industrial automation learning outcomes. The research design used was a one-group pretest posttest pre-experimental design. The sample group used was 66 students of industrial automation courses in the Mechanical Engineering Vocational Education Study Program. The research method used is the T test. The T test is used to determine the average posttest value. The level of statistical significance used is 5% (alpha). From the results of the study, it was found that there was an increase in insight related to transport equipment; storage systems; unitizing equipment; identification and tracking systems; and automatic identification and data capture (AIDC). The use of quizizz media has a role in active, interactive, fun, and modern learning in the era of digitalization.